CELL growth and viability analysis in poli membranes (L-lactic acid-CO-glycolic acid): an in vitro study - Daniel Facó da Silveira SANTOS; Jéferson Martins Pereira Lucena FRANCO; Felipe Gomes XAVIER; Aguedo ARAGONES; Carlos Clessius Ferreira XAVIER; Antonio Marcos MONTAGNER (Faculdade São Leopoldo Mandic, 2019)
Objective: Performing an in vitro evaluation of the biological effects on cell growth and viability of fibroblasts in PLGA membranes with and without simvastatin. Methods: Two groups of resorbable synthetic polymeric membranes were used: PLGA, with and without simvastatin, cut into a suitable format to fit to 24 thermometric wells. Fibroblasts were grown on resorbable membranes and evaluated for proliferation and viability at 24, 48 and 72 hours after the beginning of cultivation, being the tests performed in triplicate. For the cell growth analysis, the Trypan blue exclusion method was applied, while cell viability was observed by the MTT test. The results were statistically analyzed applying the Two-Way ANOVA, followed by the Bonferroni test, with 95% confidence interval and P value smaller than 0.05 was accepted as statistically significant. Results: Statistical difference (p <0.01) was seen between the control group (2.16x104 ± 0.51 cells) and the PLGA group with simvastatin (1.58x104 ± 0.36 cells) in the 48-hour period. After 72 hours, statistical differences (p <0.001) were observed between the PLGA group with simvastatin (1.66x104 ± 0.49 cells) and the PLGA group without simvastatin (2.25x104 ± 0.2 cells) when compared to the control group (2.81x104 ± 0.33 cells) for cell proliferation. Statistical differences (p <0.05) were observed between the control group (0.27 ± 0.05) and the PLGA group with simvastatin (0.21 ± 0.03). Likewise, a statistical difference (p <0.001) was seen between the PLGA group without simvastatin (0.19 ± 0.02) and the control group after 24 hours. In the 48 - 72-hour period, statistical differences (p <0.001) were observed between the control group (0.36 ± 0.09 and 0.55 ± 0.05, after 48 and 72 hours respectively) and the PLGA group without simvastatin (0.26 ± 0.05 and 0.34 ± 0.07, after 48 and 72 hours respectively), as well as in the PLGA group with simvastatin (0.27 ± 0.04 and 0.31 ± 0, 04, after 48 and 72 hours respectively) for the cell viability test. Conclusion: The association of simvastatin to PLGA membranes had an inhibitory effect on fibroblast proliferation, as well as induced a reduction in cell viability. Thus, the use of PLGA along with simvastatin may assist in guided bone regeneration.